Sustainable and cleaner production of poly-gamma-glutamic acid (γ-PGA) biopolymer using floral waste and its anti-staling properties - Nair, Pranav G.; Dharne, Mahesh S. (Journal of Cleaner Production, 2023)
The framework of sustainable development (SD) hinges on 17 different ideals established by the United Nations. This call for SD can be addressed by the circular bio-economy concept, which not only ensures effective waste management but also encourages its valorization and repurposing, hence fostering both ecological and economic stability. One-third of the world's floral production is in jeopardy, and because there are no potential solutions for sustaining floral waste, it inevitably ends up in landfills and riverine systems, which is detrimental to the environment. Therefore, in the present study, floral waste that was destined for landfills or water bodies was productively valorized to poly gamma glutamic acid (gamma-PGA), a high value biopolymer, with a yield of 40 g/L and productivity of 1.6 g/L/h employing an L-glutamic acid (L-GA) independent feeding approach. When gamma-PGA was coated onto Vitis vinifera grapes, it exhibited excellent moisture retention, reduced microbial contamination, and preserved the grapes' aesthetic characteristics and nutrient content. The weight loss study demonstrated that grapes coated with 1% and 2% gamma-PGA experienced significantly lower weight loss (13% and 14% respectively) compared to the control group (21.6%). Moreover, a 5-min dip coating time proved to be the most effective in reducing weight loss to 12.43%. Over a period of 14 days, the control group exhibited a remarkably high weight loss (41%) in contrast to the treated group, which showed significantly lower weight loss (16%). Our work is a fine example of how the circular bio-economy and waste valorization may be used to achieve the long-term objectives of sustainable development, economic stability, and food security.
Keywords: Bio-economy; Floral waste; L-GA independent; Poly-gamma-glutamic acid; Valorization